AN AWARENESS-RAISING APPROACH TO TEACHING SMALL TALK IN AN EFL CLASSROOM - Wang, Jing (PUPIL: International Journal of Teaching, Education and Learning, 2020)
This study investigates the effects of pragmatic awareness-raising activities in foreign language settings. Drawing on conversation analysis, we explore the pedagogical possibility of using small talk video clips as sources for an awareness-raising activity in an EFL classroom. An instruction procedure is introduced to teach small talk, particularly conversation starter and topic management. 45 Chinese college students’ role play performances were examined. The analyses show that using authentic instructional materials has a positive effect on teaching and learning pragmatic aspects of the target language. Through the pragmatic awareness-raising activities, learners may become aware of the underlying sociopragmatic norms and thus produce the relevant interactional sequence structures in English